Secreted proteases of Trypanosoma brucei gambiense: Possible targets for sleeping sickness control?. (29th March 2013) - Bossard, Géraldine; Cuny, Gérard; Geiger, Anne
Abstract : Human African trypanosomiasis (HAT) is caused by trypanosomes of the species Trypanosoma brucei and belongs to the neglected tropical diseases. Presently, WHO has listed 36 countries as being endemic for sleeping sickness. No vaccine is available, and disease treatment is difficult and has life‐threatening side effects. Therefore, there is a crucial need to search for new therapeutic targets against the parasite. Trypanosome excreted‐secreted proteins could be promising targets, as the total secretome was shown to inhibit, in vitro, host dendritic cell maturation and their ability to induce lymphocytic allogenic responses. The secretome was found surprisingly rich in various proteins and unexpectedly rich in diverse peptidases, covering more than ten peptidase families or subfamilies. Given their abundance, one may speculate that they would play a genuine role not only in classical "housekeeping" tasks but also in pathogenesis. The paper reviews the deleterious role of proteases from trypanosomes, owing to their capacity to degrade host circulating or structural proteins, as well as proteic hormones, causing severe damage and preventing host immune response. In addition, proteases account for a number of drug targets, such drugs being used to treat severe diseases such AIDS. This review underlines the importance of secreted proteins and especially of secreted proteases as potential targets in HAT‐fighting strategies. It points out the need to conduct further investigations on the specific role of each of these various proteases in order to identify those playing a central role in sleeping sickness and would be suitable for drug targeting. © 2013 BioFactors, 39(4):407–414, 2013